2011
DOI: 10.22201/iibi.0187358xp.2010.51.24330
|View full text |Cite
|
Sign up to set email alerts
|

Posicionamiento de las bibliotecas universitarias peruanas en los medios de comunicación

Abstract: muchas bibliotecas (o universidades) tienen oficinas de imagen institucional. Estas ocurrencias están distribuidas entre 17 universidades de un total de 98 existentes en el país lo cual demuestra que aún no hay una corriente que fomente el posicionamiento de estas bibliotecas.Palabras clave: Bibliotecas universitarias; medios de comunicación masivos; Perú; publicidad; posicionamiento; redes sociales; Web 2.0. Abstract Positioning of peruvian university libraries in mass media Alonso Estrada Cuzcano and Roxana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, brother 2 had only RP and polydactyly. A second study that investigated the phenotypic spectrum of the common p.M390R BBS1 variant found biallelic inheritance in two siblings with nonsyndromic RP [28]; one patient who was compound heterozygous for the p. There was only 1 patient with classic BBS in that study. A study of Saudi patients with RP found 4 patients in 1 family to be homozygous for the missense mutation, p.A89V in the BBS3 gene [30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, brother 2 had only RP and polydactyly. A second study that investigated the phenotypic spectrum of the common p.M390R BBS1 variant found biallelic inheritance in two siblings with nonsyndromic RP [28]; one patient who was compound heterozygous for the p. There was only 1 patient with classic BBS in that study. A study of Saudi patients with RP found 4 patients in 1 family to be homozygous for the missense mutation, p.A89V in the BBS3 gene [30].…”
Section: Discussionmentioning
confidence: 95%
“…It is likely that with advancing age the male patient would have shown symptoms of his retinal dystrophy. Nonsyndromic RP or RP with minimal systemic features has been described in patients with mutations in six of the BBS genes (BBS1, BBS3/RP55/ARL6, BBS8/RP51/TTC8, BBS9, BBS12, and BBS14/CEP290) [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%